The Influence Of Profitability, Leverage, Capital Intensity And Audit Committee On Tax Avoidance - Hidayat, Mardi; Kurniawan, Rahmad (Accounting and Business Journal, 2024)
This research aims to test and prove the influence of profitability, leverage, capital intensity and audit committee on tax avoidance. The research was conducted using quantitative methods involving 10 companies listed on the Indonesian Stock Exchange (BEI) for the period 2019 to 2022. The results of this study show that partially, profitability, leverage, capital intensity and audit committees have no effect on tax avoidance . Likewise, simultaneously, profitability, leverage, capital intensity and audit committee have no effect on tax avoidance. These findings imply that there are no other variables that can influence tax avoidance in producing company financial reports. This research contributes as a means of broadening horizons and increasing knowledge about tax avoidance, as well as producing additional information and becoming a reference for further research related to tax avoidance, especially those that use the same variables.